Sustainable Urban Public Squares - Javadi, Homa (European Journal of Sustainable Development, 2016)
Urban public spaces have had a prominent role in social and economic life of people. Among different types of urban public spaces, square has always played a central role through the history of urbanity and urban life. Square is a mixed-use and multi-dimensional environment, where all kinds of activities including social, political, religious, environmental, economical, etc. are taken place there. A place designed for all people from different social levels and incomes. Accordingly, to understand how a square could serve urban life efficiently and improve the quality of urban life, the concept of sustainable squares should be considered. As it is clear, sustainability deals with society, environment, and economy. Therefore, when the term of sustainability is merged with urban squares, it is necessary to investigate how an urban square could be sustainable and serve the sustainability of urban communities. To do so, in this study through seminal literature the concept of urban public square and the principals of its designing are defined. Then, the indicators making an urban square environmentally, socially, and economically sustainable are determined. Keywords: Urban Public Square, Sustainability, Physical Environment, Society, Economy